Strengthening Corporate Governance Through Legal Compliance and Ethical Codes of Conduct - Bambang Eko Turisno; Ery Agus Priyono; Yunanto Yunanto (Jurnal Hukum, 2024)
This study investigates the role and implementation of a company's code of ethics as a cornerstone of good corporate governance. The research aims to examine the contents of corporate codes of ethics, the enforcement of sanctions for violations, and the mechanisms for preventing actions that contravene ethical standards. The code of ethics serves as a guiding framework for employees, fostering professionalism, integrity, and commitment. It encapsulates normative ethics and facilitates the practical application of corporate values in daily activities. Findings reveal that the structure and content of codes of ethics vary across organizations, ranging from concise to highly detailed formats. Employees affirm their adherence through integrity and compliance pacts, establishing a mutual agreement on the disciplinary measures for breaches. Sanctions for violations are proportionate to the nature of the offense and may include multiple forms of disciplinary action. An appeal mechanism and oversight by designated supervisors ensure the fair implementation of sanctions. Furthermore, the Board of Directors plays a pivotal role in exemplifying ethical behavior and reinforcing compliance through decisive actions. This research underscores the importance of a well-defined and enforced code of ethics in fostering an ethical corporate culture and ensuring accountability within organizations.